Bioavailability and pharmacokinetics of ofloxacin in healthy volunteers. - Yuk, J H (1991)
The pharmacokinetics and bioavailability of ofloxacin in 20 healthy male volunteers were studied in an open-label, randomized, two-way crossover study. Ofloxacin (400 mg) was administered either as a 1-h infusion or as an oral tablet. The mean peak concentration after intravenous infusion was 4.30 +/- 0.69 microgram/ml, and that after oral administration was 3.14 +/- 0.53 microgram/ml, occurring 1.74 +/- 0.57 h after dosing. The bioavailability (F) of the oral dosage form of ofloxacin was virtually identical to that of the intravenous form (F = 105% +/- 7%). This complete bioavailability of ofloxacin is supportive of the use of the oral dosage form for the treatment of infections in hospitalized patients either as a replacement for intravenous ofloxacin therapy or in streamlining therapy from the intravenous to the oral route.